Barreiras regulatórias: A infraestrutura da qualidade no México, no Chile e na Colômbia em comparaç\~ao com Brasil e Argentina - Vera Thorstensen; Mauro Kiithi Arima Júnior; Tiago Matsuoka Megale; Fábio Jorge de Toledo Thomazella (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The purpose of this paper is to examine, from the perspective of international trade, the general characteristics of the operation of technical regulations, technical standardization and conformity assessment procedures (quality infrastructure) adopted by Chile, Mexico and Colombia. Next, the researchers will try to identify, from a perspective that relates trade to quality infrastructure, similarities and differences between these three countries and the two main members of Mercosur: Brazil and Argentina. The conclusions will emphasize the importance of regulatory barrier and convergence initiatives to international trade.
Keywords: F10; F13; F15; 330; Mexico; Chile; Colombia; regulatory barriers; technical regulation; standard; conformity assessment; international trade